2013
DOI: 10.2319/020413-103.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of effects of rapid maxillary expansion on facial sutures and bones: A systematic review

Abstract: CT imaging proved to be a useful tool for assessment of treatment effects in all three dimensions. The majority of the articles were judged to be of low quality, and therefore, no evidence-based conclusions could to be drawn from these studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 20 publications
8
93
1
2
Order By: Relevance
“…Out of the tested demographic and dentofacial variables, no significant correlation with the risk of asymmetric expansion was found except for the chin deviation (Table ). Moreover, unilateral splits of other circum‐maxillary sutures or transverse palatal sutures, occasionally observed in patients of Group A, could not be statistically investigated in this study due to the large interindividual variations and low incidence . The clinical implication is that a facial asymmetric patient with chin deviation has a risk of asymmetric expansion with TBB‐RPE, and thus, facial asymmetry may be alleviated or aggravated unpredictably.…”
Section: Discussionmentioning
confidence: 95%
“…Out of the tested demographic and dentofacial variables, no significant correlation with the risk of asymmetric expansion was found except for the chin deviation (Table ). Moreover, unilateral splits of other circum‐maxillary sutures or transverse palatal sutures, occasionally observed in patients of Group A, could not be statistically investigated in this study due to the large interindividual variations and low incidence . The clinical implication is that a facial asymmetric patient with chin deviation has a risk of asymmetric expansion with TBB‐RPE, and thus, facial asymmetry may be alleviated or aggravated unpredictably.…”
Section: Discussionmentioning
confidence: 95%
“…The 12 SRs/MAs included and the data extracted are reported in Table . Four SRs were integrated with MA .…”
Section: Resultsmentioning
confidence: 99%
“…Skeletal transversal effects of RME : With the Haas or Hyrax appliance, an increase in the distance between the left and right jugale points ( low evidence), an increase in the dimension of the posterior and anterior region of the midpalatal suture ( low evidence) and an increase in the dimension of the canine region ( low evidence) were found.…”
Section: Resultsmentioning
confidence: 99%
“…Pertinent studies became available following the introduction of CBCT to dentistry-and orthodontics [38]-in the late 1990s [52]. More recently, systematic reviews of CBCT studies on RME have become available [5,9,21,27,37,39,[57][58][59]. Given the natural advantages of CBCT, these studies have mainly reported on changes in the transverse plane, but maxillary movements in caudal and anterior directions have also been described [27].…”
Section: Discussionmentioning
confidence: 99%